Concepciones en una zona rural andina con respecto al significado del embarazo, parto y puerperio - Benites Jara, Wilson Alberto (2010)
This qualitative research was conducted ethnographic path in Marcabal district, province of Sánchez Carrión, aiming sizing the conceptions regarding the cultural significance of pregnancy, childbirth and postpartum and analyze the implications from the standpoint of culture care health of women. The participants were 16 key informants who were respectively conducted the interview, which was recorded. Also took field notes to supplement the data. An analysis of the discourses identified 13 cultural domains, with the reference to Spradley (1979) and Leininger (1985), taxonomies built led to the theme and sub-themes: Being in harmony with nature, my family and myself and respecting our beliefs, habits ... is to run a successful pregnancy and give birth safely ... We let the midwife attend us and guide us ... their knowledge, experience and practices during childbirth give us peace, then we give birth to follow the advice from the midwife, my family attends and takes care of me ... to regain my strength ... so all the time, and a sub theme, which mirrors the concepts with respect to the cultural significance of pregnancy, childbirth and puerperium of rural women, expressing holistic concepts and practices that are considered common sense, transmitted generationally and emphasizing Family involvement in your care. Objective is respect for their worldview and nature, and the anchoring of care is rooted in their customs, beliefs, symbols and images that govern the behavior of its people, this affect maternal and child health.